STRATEGIES FOR CONCENTRATION AND RATIONALIZATION OF HERITAGE IN THE 16TH AND 17TH CENTURIES: CELIBACY AND CONSANGUINITY OF THE MUÑOZ DE OTÁLORA IN THE TOWN OF CARAVACA (SPAIN) - Martínez Martínez, José Antonio (Revista de Historia Social y de las Mentalidades, 2021)
The aim of this article is to analyze the strategies of concentration and rationalization of patrimony through celibacy and marriage practices of the Muñoz de Otálora family. Celibacy is presented as a strategy, frequently used by the powerful to avoid the dispersion of patrimony through the resignations of the legitimate nuns and the future inheritances of priests. In contrast, marriage is analyzed in terms of social reproduction and consanguineous marriages, as a defensive tool for lineage and heritage. We can observe that the families of power at the time of choosing a spouse paid as much importance to the place where the bulk of the possessions resided as to the amount of the dowries. The combination of both strategies, celibacy and consanguineous marriages, allowed the social reproduction of the family, but not the biological reproduction of the main branches of the lineage
Keywords: Marriage; Celibacy; Wealth Concentration; Wealth Rationalization; Family